2020
DOI: 10.4274/tjod.galenos.2020.12129
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions toward and the driving factors of decision-making for opportunistic bilateral salpingectomy at the time of cesarean section

Abstract: Objective: Enough data can be found in the literature regarding the protective effect of tubal ligation on gynecological cancers. In addition, a large body of evidence revealed that prophylactic bilateral salpingectomy had no significant negative effect on the ovarian function, quality of life, sexuality, surgery duration, and cost-effectivity. This study was aimed at exploring the underlying factors that motivate women for either opportunistic bilateral salpingectomy (OBS) or tubal ligation, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…5 Since prophylactic BS was shown to have more significant cancer risk reduction than BTL without significantly increasing complication rates and decrease in ovarian function, 1 performing BS for definitive surgical sterilization is emerging, although it is still uncommon. 4,8 In a large population-based retrospective cohort study, although a significant increase was reported in the use of isolated BS for sterilization, there was no difference in surgical approach during the evaluated tme period. 6 The advantages of vaginal surgery are more favorable over other approaches in benign gynecological diseases.. 17,18 However, the limitations of pure vaginal surgery such as insufficient visualization of the surgical field and difficulty in accessing adnexal structures in non-prolapsed uterus restrict the utilization of transvaginal opportunistic BS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Since prophylactic BS was shown to have more significant cancer risk reduction than BTL without significantly increasing complication rates and decrease in ovarian function, 1 performing BS for definitive surgical sterilization is emerging, although it is still uncommon. 4,8 In a large population-based retrospective cohort study, although a significant increase was reported in the use of isolated BS for sterilization, there was no difference in surgical approach during the evaluated tme period. 6 The advantages of vaginal surgery are more favorable over other approaches in benign gynecological diseases.. 17,18 However, the limitations of pure vaginal surgery such as insufficient visualization of the surgical field and difficulty in accessing adnexal structures in non-prolapsed uterus restrict the utilization of transvaginal opportunistic BS.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The fact that opportunistic BS during cesarean section provides a lower risk of ovarian cancer and superior contraception than BTL makes women accept this procedure at rates as high as 93.5% compared to BTL. 8 Opportunistic BS or BTL can be traditionally performed by laparoscopic, abdominal or vaginal routes commonly following any other gynecological procedures. 2 Considering the theoretical benefits of opportunistic BS, The American College of Obstetricians and Gynecologists (Committee opinion No.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the incidence of opportunistic salpingectomy in conjunction with hysterectomy appears to have increased substantially the past 10 years [19,20]. Recent studies indicate that women have a high acceptance for salpingectomy, also in combination with non-gynaecological procedures [20,21]. Several societies have issued statements supporting opportunistic salpingectomy at the time of hysterectomy on benign indications [22e24].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2020 prospective cohort study of 54 women, Yassa and Pulatoğlu 61 found that the acceptance rate of salpingectomy at the time of cesarean delivery was 94% and that the acceptance rate of salpingectomy as an elective procedure among nonpregnant women was 75%. They found that the main factors associated with the preference for salpingectomy vs tubal ligation were ovarian cancer prevention and superior pregnancy prevention.…”
Section: Public Perceptionmentioning
confidence: 99%